High Precision, Electrochemical Detection of Reversible Binding of Recombinant Proteins on Wide Bandgap GaN Electrodes Functionalized with Biomembrane Models. (13th May 2014) - Frenkel, Nataliya; Wallys, Jens; Lippert, Sara; Teubert, Jörg; Kaufmann, Stefan; Das, Aparna; Monroy, Eva; Eickhoff, Martin; Tanaka, Motomu
<x xml:space="preserve">Abstract</x> We report a novel hybrid charge sensor realized by the deposition of phospholipid monolayers on highly doped n‐GaN electrodes. To detect the binding of recombinant proteins with histidine‐tags, lipid vesicles containing chelator lipids were deposited on GaN electrodes pre‐coated with octadecyltrimethoxysilane monolayers. Owing to its optical transparency, GaN allows the confirmation of the fluidity of supported membranes by fluorescence recovery after photo‐bleaching (FRAP). The electrolyte‐(organic) insulator‐semiconductor (EIS) setup enables one to transduce variations in the surface charge density ΔQ into a change in the interface capacitance ΔCp and, thus, the flat‐band potential ΔUFB. The obtained results demonstrate that the membrane‐based charge sensor can reach a high sensitivity to detect reversible changes in the surface charge density on the membranes by the formation of chelator complexes, docking of eGFP with histidine tags, and cancellation by EDTA. The achievable resolution of ΔQ ≥ 0.1 μC/cm2 is better than that obtained for membrane‐functionalized p‐GaAs, 0.9 μC/cm2, and for ITO coated with a polymer supported lipid monolayer, 2.2 μC/cm2. Moreover, we examined the potential application of optically active InGaN/GaN quantum dot structures, for the detection of changes in the surface potential from the photoluminescence signals measured at room temperature.